Commercialization of innovations through internationalization: A systematic literature review - Klaudia Bracio; Marek Szarucki (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The main purpose of the article is to identify the state of knowledge between two multidimensional phenomena: commercialization of innovation and internationalization. In terms of research methods, a systematic literature review, based on the 91 publications located in reputable scientific databases (Scopus and Web of Science) between the years 2000-2017 and Rapid Automatic Keyword Extraction (RAKE), was applied. The main findings provide information on the concept of commercialization of innovations via internationalization, and specifically on different research perspectives and areas of analysis with division of the bibliometric data. The selection of the articles for further analysis is perceived as the main limitation of this study, as some papers may not have been included due to missing keywords or due to having been absent from the two selected databases. The article analyses theoretical research and empirical papers and enables identification of problems in the current research as well as identifying trends in the area of the studied phenomenon. The results on the topic of commercialization of innovation through internationalization have indicated that this issue is still in a premature phase but with an upward trend of research development.
Keywords: O00; D83; B49; L17; 650; innovations; commercialization of innovation; internationalization; research trends; systematic literature review